2015
DOI: 10.1007/s11552-014-9730-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Four Recruitment Methods for Obtaining Normative Data through a Web-Based Questionnaire: A Pilot Study

Abstract: Background Quality normative data requires a diverse sample of participants and plays an important role in the appropriate use of health outcomes. Using social media and other online resources for survey recruitment is a tempting prospect, but the effectiveness of these methods in collecting a diverse sample is unknown. The purpose of this study is to pilot test four methods of recruitment to determine their ability to produce a sample representative of the general US population. Methods This project is part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
(44 reference statements)
4
29
0
Order By: Relevance
“…Due to these challenges and more, alternative recruitment strategies that differ from initially proposed methods may be developed when recruitment goals are unmet. Different recruitment methods have been utilized in studies addressing various research questions, among different populations (Lane et al, 2015;Nolte, Shauver, & Chung, 2015;Williams et al, 2011). However, it is important for researchers to recognize the need for recruitment approaches to be germane to the population of interest, the research design and methodology, the location and demographic characteristics of participants, and the feasibility of designated approaches (Newington & Metcalfe, 2014;Nolte et al, 2015).…”
Section: Recruitment In Community Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to these challenges and more, alternative recruitment strategies that differ from initially proposed methods may be developed when recruitment goals are unmet. Different recruitment methods have been utilized in studies addressing various research questions, among different populations (Lane et al, 2015;Nolte, Shauver, & Chung, 2015;Williams et al, 2011). However, it is important for researchers to recognize the need for recruitment approaches to be germane to the population of interest, the research design and methodology, the location and demographic characteristics of participants, and the feasibility of designated approaches (Newington & Metcalfe, 2014;Nolte et al, 2015).…”
Section: Recruitment In Community Studiesmentioning
confidence: 99%
“…For example, researchers using flyers and social media have shown that it is useful in reaching older and younger participants ODOH ET AL. | 447 respectively, whereas community member inclusion and word of mouth may be particularly effective among African Americans or marginalized groups (Nolte et al, 2015;Whitaker, Stevelink, & Fear, 2017;Williams et al, 2011). Ultimately, recruitment efforts in this study were informed by known methods, community input, experiences from a previous coal ash pilot study, study design, and suitability of recruitment strategies (Whitaker et al, 2017;Williams et al, 2011;Zierold & Sears, 2015 (Martin, 2009).…”
Section: Recruitment In Community Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, elderly have little chance to be sampled at all. Other, more traditional methods such as flyers have the problem of respondents not having a direct and convenient access to the survey and may result in a smaller recruitment rate [19]. The PASTA Project (Physical Activity through Sustainable Transport Approaches) [20,21], used a combination of different opportunistic recruitment methods in order to utilize strengths and to minimize weaknesses.…”
Section: Introductionmentioning
confidence: 99%